Image_3.jpg - Mumbai Archive Project Team (Jio Institute, 2024)
Koli women are actively involved in various economic activities related to fishing and maritime livelihoods and play a central role in maintaining the household in the absence of male family members who are away at sea. In addition to taking care of their household affairs, they run small businesses that add to the family income.